Which obstetrics-gynecology residency programs are training future reproductive endocrinology and infertility fellows? An observational study - Zachary S. Anderson, M.D; Erika P. New, M.D; Aaron D. Masjedi, M.D; M. Blake Evans, D.O (Elsevier, 2024)
Objective: To identify where reproductive endocrinology and infertility (REI) fellows trained for residency. Design: Observational, cross-sectional study. Setting: Not applicable. Subject(s): Reproductive endocrinology and infertility fellows. Intervention(s): Not applicable. Main Outcome Measure(s): Percentage of fellows who completed residency training at an institution with an REI fellowship program. Result(s): A total of 289 fellows were identified among the graduating fellowship classes from 2023-2027. Of those fellows, 69.9% completed residency at an institution that had an associated REI fellowship program, and 19.7% remained at the same institution for residency and fellowship. In the last 5 years, 34.4% of obstetrics and gynecology residency programs have had at least 1 resident enter REI fellowship. Conclusion(s): Most matriculated REI fellow physicians train at residency programs that have an associated REI fellowship program.